2020
DOI: 10.1002/jcp.29950
|View full text |Cite
|
Sign up to set email alerts
|

The expanding role of CDR1‐AS in the regulation and development of cancer and human diseases

Abstract: CircRNAs are a superabundant and highly conserved group of noncoding RNAs (ncRNAs) that are characterized by their high stability and integrity compared with linear forms of ncRNAs. Recently, their critical role in gene expression regulation has been shown; thus, it is not far-fetched to believe that their abnormal expression can be a cause of different kinds of diseases such as cancer, neurodegenerative, and autoimmune diseases. They can have a function in variety of biological processes such as microRNA (miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 118 publications
0
9
0
Order By: Relevance
“…We thus found that particular miRNAs, such as miR-671-5p, ciRS-7-5p, and miR-122-5p, are consistently deregulated throughout AD progression. A previous study that found molecular mechanisms of ciRS-7 depletion in AD suggested that ciRS-7 could be an AD treatment target ( 20 ). Similarly, we present results for lesser-known miRNA circulating in AD tissue samples.…”
Section: Resultsmentioning
confidence: 99%
“…We thus found that particular miRNAs, such as miR-671-5p, ciRS-7-5p, and miR-122-5p, are consistently deregulated throughout AD progression. A previous study that found molecular mechanisms of ciRS-7 depletion in AD suggested that ciRS-7 could be an AD treatment target ( 20 ). Similarly, we present results for lesser-known miRNA circulating in AD tissue samples.…”
Section: Resultsmentioning
confidence: 99%
“…CDR1as is a closed circular RNA formed from the antisense transcript of the cerebellum degeneration-related antigen 1 (CDR1) gene, whose length is 1,485 bp (Hansen et al, 2013b). CDR1as is highly expressed in the human brain and plays a vital role in midbrain development (Memczak et al, 2013), which might account for its relationship with neurodegenerative diseases, such as Alzheimer and Parkinson's disease (Shi et al, 2017;Azari et al, 2020). And the overexpression of CDR1as in zebrafish resulted in defects in the midbrain region similar to the knockdown of miR-7 (Memczak et al, 2013).…”
Section: The Biological Functions Of Cdr1asmentioning
confidence: 99%
“… 6 Disease progression in human life is largely affected by circRNAs. 7 , 8 CircRNA HECT domain and ankyrin repeat containing E3 ubiquitin protein ligase 1 (circ-HACE1, hsa_circ_0077520) was shown to be upregulated in cigarette smoke extract (CSE)-induced COPD cell model, 9 but its function and underlying mechanism in COPD are still unclear.…”
Section: Introductionmentioning
confidence: 99%